Alternative treatment of recurrent skin wound in elephants (Veterinary Science, 2020)
The relationship between humans and elephants dates back thousands of years. Throughout this history, much has been learned about the management of these giants, especially in terms of behavior, health, nutrition, among other basic needs that contribute to their well-being. This made it go from being a simple tool to part of a working team. One of the main problems that can be seen in elephants kept in captivity are the skin lesions caused during their daily activities. Today, there are several works and manuals that describe the steps to follow when handling a skin wound, especially with regard to recurrent wounds in these animals, whose skin has very particular characteristics. The protocols are based on surgical procedures and systemic antibiotic therapies. The problem that arises with these procedures is the difficulty of finding suitable personnel to carry out these procedures and the drugs indicated for this purpose. The objective of this work is not only to show that there is an alternative therapy to the management of cutaneous wounds in elephants, based on the use of peloids, the main component of which is diatoms but to highlight the importance of adapting to the natural behavior of the animal so that the therapy has positive results as well.
Keywords: elephant; skin wound; alternative therapy; diatoms